The Implication of the Changing Forest Management Paradigms in Formulating Forestry Policies in Kenya - Sylvester Ngome Chisika; Chunho Yeom (Forestist)
Forests and related environmental assets are crucial for fostering environmental and socioeconomic development. Different forest management paradigms, such as sustainable forest management, ecosystem-based forest management, adaptive management, multiple-use forest management, and restoration ecology, have influenced the policy formulation of different countries at different times. However, while implementing forestry development reforms, few documented studies have explored the changing forest management paradigms and their implications on the sustainability of forests and societies in many developing countries. A case study design and literature review using document-content analysis was used to evaluate secondary data obtained from online sources. This paper aims to explore the changes in forest management paradigms in Kenya from 1968 to the present to contribute to a better understanding of the strategies needed to achieve sustainable forest management in the future. Results show that Kenya has implemented three formal forestry policies since independence in 1963. These include Sessional Paper No. 01 of 1968, Forest Policy of 2005, and the National Forest Policy of 2014. The evolving forest management paradigm reflects a progression from Sessional Paper No. 01 of 1968 to subsequent forest policies in 2005 and 2014. The 2005 and 2014 forest policies emphasize holistic ecosystem management and ecosystem services and integrate a human rights-based approach to community involvement. Moreover, all three forest policies have had positive and negative implications for Kenyan society. The Forest Policy and the National Forest Policy demonstrated more positive environmental and socioeconomic outcomes, such as increased forest cover, biodiversity conservation, community empowerment, poverty alleviation, and improved transparency compared to the Sessional Paper No. 01 of 1968. Unfortunately, some negative consequences include conflicting stakeholder interests, elite capture, and slow decision-making. Based on these findings, there is a need for policy impact assessment, addressing the adverse effects of policy, and long-term monitoring for sustainable future forest policies.